The development of a Bachelor of Laws (LLB) curriculum change management model for South African universities - Moolman, Hermanus Johannes (Department of Private Law, 2023)
The National Review of the LLB by the Higher Education Qualifications Committee of the Council on Higher Education from 2015 to 2018 underscored the dire need for LLB curriculum change at South African universities. Not only did the Review call for ‘wideranging curriculum reform', but it also recommended that the minimum duration of the four-year LLB be extended by an additional year. Most institutions responded with minor changes to their LLB curricula to meet the demands of the National Review of the LLB and to remain accredited. However, a comprehensive review of their LLB curricula may be required to improve the quality of their graduates in the long run. Furthermore, should it be decided to extend the LLB by one year, all universities offering a four-year LLB will have to engage in comprehensive curriculum change by developing new five-year LLB curricula. Although curriculum change management models (hereafter CCMMs) play an important role in revising or reflecting on HE curriculum change, no model was available for law curriculum change. The study focuses on developing a change management model for facilitating comprehensive curriculum change of the LLB at universities in South Africa. A mixed methods research design was adopted to achieve the purpose of the study. Based on a literature review, a Draft LLB CCMM comprising 61 prescriptive outlines (hereafter POs) was proposed in Phase 1. The Draft LLB CCMM was used to compile a structured questionnaire in Phase 2 of the study. Staff members (n=28) who had participated in a comprehensive LLB curriculum change process at the University of the Free State (hereafter UFS) quantitatively rated the importance of the POs for facilitating LLB curriculum change in South African circumstances. They also rated the compliance of the UFS curriculum change process with these POs. The quantitative evaluation of the POs of the Draft LLB CCMM in terms of importance suggested that all POs should be included in the Final LLB CCMM. A critical reflection on the initiatives and practices implemented during the UFS curriculum change process led to identifying recommended practices for those POs that met the minimum quantitative compliance criteria. Reflective appraisal, the quantitative feedback from questionnaire participants and consulting appropriate literature assisted in identifying what could have been done differently for those POs that did not meet the minimum compliance criteria. Also, a focus group discussion in Phase 3 shed light on why some POs did not meet the minimum compliance criteria. In the focus group, the discussions on the strengths and weaknesses of the UFS curriculum change process led to the identification of additional POs and recommended practices in the Final LLB CCMM. The quantitative and qualitative findings in Phases Two and Three were integrated to propose the Final LLB CCMM. The study contributes towards curriculum change theory building. The Final LLB CCMM breaks down the challenging, multifaceted and complex nature of comprehensive curriculum change into manageable processes, functions, POs and recommended practices. Although the CCMM was specifically developed for comprehensive LLB curriculum change, specific processes, functions, or POs of the model can be adapted to permit faculties to engage in minor or piecemeal LLB curriculum changes. Also, the CCMM can be adapted to facilitate curriculum change in other disciplines.